Association of white matter hyperintensity burden and infarct volume in the anterior choroidal artery territory with early neurological progression: a dual-center retrospective study - Gao, Weiwei; Wang, Lixue; Huang, Junyi; Yu, Yitao; She, Jingjing; Wang, Mingyang; Cai, Lijuan; Kang, Taishan; Chen, Xingyu; Lin, Jianzhong; Zhu, Renjing (Frontiers in Aging Neuroscience, 2025)
ObjectiveTo investigate the associations of white matter hyperintensity (WMH) burden and infarct volume with early neurological progression in anterior choroidal artery (AChA) territory infarction, and to identify potential imaging-based predictive thresholds.MethodsThis retrospective cohort study consecutively enrolled AChA infarct patients admitted to two comprehensive stroke centers between September 2018 and September 2024. WMH burden and infarct volume were assessed using the Fazekas visual rating scale and an automated volumetric quantification method based on lesion prediction algorithm, respectively. The primary outcome was early neurological progression. Multivariate logistic regression models with stepwise adjustment for confounders were used to evaluate the associations of WMH burden and infarct volume with early progression. Restricted cubic spline regression was performed to explore non-linear relationships and to determine thresholds. Continuous variables were standardized, and piecewise regression analysis was conducted based on the identified thresholds. Subgroup analyses with interaction tests were performed to assess the consistency of these associations across different populations.ResultsA total of 216 patients were included, of whom 82 (38.0%) experienced early neurological progression. After adjustment for potential confounders, WMH burden showed a significant non-linear association with progression risk. For WMH volumes <66.1 mL, each standard deviation increase was associated with a 74% higher risk of progression (standardized OR: 1.74, 95% CI: 1.29–2.40, p < 0.001). Compared with the lowest quartile, patients in the highest WMH quartile showed significantly increased risk (adjusted OR: 5.32, 95% CI: 1.48–13.88, p = 0.009). This association was confirmed by Fazekas scale analysis, with grade 3 patients showing substantially higher risk than grade 0 (adjusted OR: 6.22, 95% CI: 1.74–25.42, p = 0.007). Infarct volume demonstrated a similar non-linear pattern; for volumes <1.1 mL, each standard deviation increase was associated with 59% higher progression risk (standardized OR: 1.59, 95% CI: 1.04–2.47, p = 0.036). Quartile analysis revealed the highest risk in the third quartile compared to the lowest (adjusted OR: 5.63, 95% CI: 2.06–15.40, p < 0.001).ConclusionThis study revealed non-linear associations of WMH and infarct volume with early progression in AChA infarct patients.